1999
DOI: 10.1080/08964289909596735
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Emotional Expression in Breast Cancer Patients

Abstract: To obtain a better understanding of the inhibited emotional expression often reported in breast cancer patients, the authors compared 48 breast cancer patients and 49 healthy women with respect to disturbed emotional processes (alexithymia), emotional disclosure, emotional expression, assertiveness, repression, and distress. The patient group showed significantly more ambivalence over emotional expression, more restraint, and more anxiety than the healthy controls. No differences were found between the 2 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 13 publications
6
36
0
3
Order By: Relevance
“…It is a one-dimensional scale composed of 16 items (e.g., "When I am angry people around me usually know") scored on a 7-point Likert-type scale ranging from 1 (strongly disagree) to 7 (strongly agree). One study reported information regarding internal consistency (α = .80) (Servaes et al, 1999). Similar reliabilities have been found in other studies with different populations (e.g., α = .74 in a sample of college students; α = .77 in a sample of young adults) (Barr, Kahn, & Schneider, 2008;Niles et al, 2013. 12.…”
Section: The Emotional Expressiveness Questionnaire (Eeq)supporting
confidence: 61%
See 4 more Smart Citations
“…It is a one-dimensional scale composed of 16 items (e.g., "When I am angry people around me usually know") scored on a 7-point Likert-type scale ranging from 1 (strongly disagree) to 7 (strongly agree). One study reported information regarding internal consistency (α = .80) (Servaes et al, 1999). Similar reliabilities have been found in other studies with different populations (e.g., α = .74 in a sample of college students; α = .77 in a sample of young adults) (Barr, Kahn, & Schneider, 2008;Niles et al, 2013. 12.…”
Section: The Emotional Expressiveness Questionnaire (Eeq)supporting
confidence: 61%
“…Four studies reported data regarding internal consistency (α's range from .69 to .73) Servaes et al, 1999;Tamagawa et al, 2013). A previous study found good one-year test-retest reliability (r = .75) (Giese-Davis & Spiegel, 2001).…”
Section: The Emotional Approach Coping Scale (Eacs)mentioning
confidence: 99%
See 3 more Smart Citations